A high entropy boride ceramic nanopowder and its preparation method and application

By using high-entropy boronide ceramic nanopowder as a catalyst, the problem of transition metals in the degradation of tetracycline in the prior art is solved, and efficient and environmentally friendly degradation effect is achieved, and it is suitable for large-scale industrial production.

CN116444276BActive Publication Date: 2024-12-17SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310289615.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2024-12-17
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

When degrading tetracycline, the prior art has problems such as transition metals being easily agglomerated, low reuse rate, and easy loss of metal ions, resulting in secondary pollution of water bodies, which is difficult to meet the practical application requirements.

Method used

High entropy boronide ceramic nanopowders are used as catalysts, and the metal oxide powder, boron oxide powder, magnesium powder and NaF are pre-pressed into mixed powder tablets, and titanium powder and carbon powder are used as ignition agents. Combustion synthesis reaction obtains high entropy boronide ceramic nanopowders, which degrade tetracycline as activated persulfate catalyst.

Benefits of technology

It has achieved efficient degradation of tetracycline, with small particle size, uniform element distribution, low oxygen impurity content, high degradation efficiency, low pollution to water, and recyclable use, suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116444276B_ABST
    Figure CN116444276B_ABST
Patent Text Reader

Abstract

The invention discloses a high entropy boride ceramic nanopowder and a preparation method and application thereof. The preparation method of the high entropy boride ceramic nanopowder of the invention comprises the following steps: pre-pressing metal oxide powder, boron oxide powder, magnesium powder and NaF into mixed powder tablets, then igniting the mixed powder tablets with an igniter to carry out a combustion synthesis reaction, and then crushing, grinding, washing and acid washing to obtain the high entropy boride ceramic nanopowder. The high entropy boride ceramic nanopowder of the invention has a small particle size, uniform element distribution, and low oxygen impurity content, and the preparation method thereof has the advantages of simple operation, low operating temperature, short reaction time, and low equipment requirements, and is suitable for large-scale industrial production. Using it as a catalyst to activate PS to degrade tetracycline has the advantages of high degradation efficiency, low water pollution, and recyclability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high entropy materials, and in particular to a high entropy boride ceramic nano powder and a preparation method and application thereof. Background Art

[0002] Tetracycline antibiotics are one of the most widely used and consumed antibiotics. They play an important role in treating human and livestock diseases and promoting livestock growth. However, tetracycline is stable and difficult to degrade in the natural environment. It will remain in the ecological environment in large quantities and has ecotoxicity. Therefore, it is of great practical value to study and develop efficient methods for degrading tetracycline.

[0003] Activated persulfate (PS) oxidation is a new type of advanced oxidation technology that has developed rapidly in recent years. It combines the advantages of being green, environmentally friendly, and economical, and is a promising environmental governance technology. Transition metal activated PS can be carried out at room temperature and pressure, and has a rapid reaction and simple operation. It is considered to be the best PS activation method, but it also has problems such as easy agglomeration of transition metals, low reuse rate of transition metals, and easy loss of metal ions causing secondary pollution of water bodies. It is difficult to fully meet the requirements of practical applications.

[0004] Therefore, it is of great significance to develop a highly stable, high specific surface area, and recyclable catalyst for efficient activation of PS to degrade tetracycline. Summary of the invention

[0005] The purpose of the present invention is to provide a high entropy boride ceramic nanopowder and a preparation method and application thereof.

[0006] The technical solution adopted by the present invention is:

[0007] A preparation method of high entropy boride ceramic nanopowder comprises the following steps: pre-pressing metal oxide powder, boron oxide powder, magnesium powder and NaF into mixed powder tablets, igniting the mixed powder tablets with an igniter to carry out combustion synthesis reaction, and then crushing, grinding, water washing and acid washing to obtain high entropy boride ceramic nanopowder; the metal oxide powder is composed of at least four of Ta2O5, Nb2O5, Cr2O3, ZrO2, TiO2 and HfO2 in an equal molar ratio; and the igniter is composed of titanium powder and carbon powder.

[0008] Preferably, a method for preparing high entropy boride ceramic nanopowder comprises the following steps:

[0009] 1) mixing metal oxide powder, boron oxide powder, magnesium powder and NaF, grinding them and pre-pressing them into sheets to make mixed powder tablets, and mixing titanium powder and carbon powder, grinding them to make an ignition agent;

[0010] 2) adding the mixed powder tablet and the igniter into a graphite mold, taking a section of molybdenum wire and passing it through the igniter, and then placing the graphite mold in a protective atmosphere, and then electrically heating the molybdenum wire to burn the igniter to ignite the mixed powder tablet to carry out a combustion synthesis reaction to obtain a combustion product;

[0011] 3) The combustion products are crushed, ground, washed with water, pickled with acid and dried to obtain high entropy boride ceramic nanopowders.

[0012] Preferably, the ratio of the total molar amount of the metal oxide powder to the molar amount of the boron oxide powder is 1:2.

[0013] Preferably, the ratio of the total molar amount of oxygen atoms in the metal oxide powder and the boron oxide powder to the molar amount of magnesium powder is 1:1.7-1.9.

[0014] Preferably, the molar ratio of the boron oxide powder to NaF is 1:2.0-3.4.

[0015] Preferably, the igniter is composed of titanium powder and carbon powder in a molar ratio of 1:1.

[0016] Preferably, the Ta2O5, Nb2O5, Cr2O3, ZrO2, TiO2 and HfO2 are all in powder form, with a purity of ≥99.9% and a particle size of 100nm to 300nm.

[0017] Preferably, the boron oxide powder has a purity of ≥99.9% and a particle size of 1 μm to 3 μm.

[0018] Preferably, the purity of the magnesium powder is ≥99.5%, and the particle size is 1 μm to 3 μm.

[0019] Preferably, the purity of the NaF is ≥98.0%; the purity of the titanium powder is ≥99.9%, and the particle size is 1 μm to 3 μm.

[0020] Preferably, the purity of the carbon powder is ≥99.0% and the particle size is <48 μm.

[0021] Preferably, the pre-compression into tablets in step 1) is carried out at a pressure of 30 MPa to 50 MPa.

[0022] Preferably, in step 2), the graphite mold is rectangular, 15 cm to 20 cm long, and 5 cm to 10 cm wide.

[0023] Preferably, the protective atmosphere in step 2) is an argon atmosphere, and the gas pressure is normal pressure.

[0024] Preferably, in step 2), the molybdenum wire has a length of 20 cm to 25 cm and a diameter of 0.4 mm to 0.6 mm.

[0025] Preferably, the current of the electric heating in step 2) is 30A to 50A, and the power-on time is 5s to 15s.

[0026] Preferably, the water washing in step 3) is carried out at 70°C to 90°C, the number of washing times is 3 to 5 times, and the time of each washing is 3 hours to 5 hours.

[0027] Preferably, the pickling in step 3) is carried out at room temperature (25°C±5°C), the acid used for pickling is hydrochloric acid with a concentration of 1 mol / L to 3 mol / L, and the pickling time is 3h to 5h.

[0028] A high entropy boride ceramic nano powder is prepared by the above preparation method.

[0029] Preferably, the average particle size of the high entropy boride ceramic nanopowder is 85 nm to 95 nm.

[0030] Preferably, the oxygen impurity content of the high entropy boride ceramic nanopowder is 2.5% to 2.9%.

[0031] Preferably, each element in the high entropy boride ceramic nanopowder is evenly distributed.

[0032] An application of the high entropy boride ceramic nanopowder as described above in the catalytic degradation of tetracycline by activated persulfate.

[0033] The invention has the following beneficial effects: the high entropy boride ceramic nanopowder of the invention has small particle size, uniform element distribution, low oxygen impurity content, and the preparation method thereof has the advantages of simple operation, low operating temperature, short reaction time, low equipment requirements, etc., and is suitable for large-scale industrial production. Using the nanopowder as a catalyst to activate PS to degrade tetracycline has the advantages of high degradation efficiency, low water pollution, and recyclability.

[0034] Specifically:

[0035] 1) The high entropy boride ceramic nanopowder of the present invention has a small particle size (average particle size of 85nm to 95nm), a spherical particle morphology, uniform element distribution, and a low oxygen impurity content (2.5% to 2.9%), which helps to improve its catalytic performance;

[0036] 2) The present invention can prepare high entropy boride nanopowders of any at least four elemental components of Ta, Nb, Cr, Zr, Ti and Hf, and the elemental composition of the high entropy boride ceramic nanopowders has a large adjustable space;

[0037] 3) The method for preparing the high entropy boride ceramic nanopowder of the present invention has the advantages of low raw material price, simple operation, low operating temperature, short reaction time, low equipment requirements, and low environmental pollution, and is suitable for large-scale industrial production;

[0038] 4) The high entropy boride ceramic nanopowder of the present invention is used as a catalyst to activate PS to degrade tetracycline, which has the advantages of high degradation efficiency (89% to 94%), little pollution to water bodies, and recyclability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 1 is the XRD diagram of the high entropy boride ceramic nanopowder in Examples 1 to 3.

[0040] Figure 2 1 is the STEM-EDS spectrum element distribution diagram of the high entropy boride ceramic nanopowder in Examples 1 to 3.

[0041] Figure 3 This is a graph showing the degradation efficiency test results of tetracycline catalytic degradation by activating PS with high entropy boride ceramic nanopowder in Examples 1 to 3. DETAILED DESCRIPTION

[0042] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0043] The purity of Ta2O5 powder, Nb2O5 powder, Cr2O3 powder, ZrO2 powder, TiO2 powder and HfO2 powder in Examples 1 to 3 is ≥99.9%, and the particle size is 100nm to 300nm.

[0044] The boron oxide powder in Examples 1 to 3 has a purity of ≥99.9% and a particle size of 1 μm to 3 μm.

[0045] The purity of the magnesium powder in Examples 1 to 3 is ≥99.5%, and the particle size is 1 μm to 3 μm.

[0046] The purity of NaF in Examples 1 to 3 is ≥ 98.0%.

[0047] The purity of the titanium powder in Examples 1 to 3 is ≥99.9%, and the particle size is 1 μm to 3 μm.

[0048] The purity of the carbon powder in Examples 1 to 3 is ≥99.0%, and the particle size is <48 μm.

[0049] Embodiment 1:

[0050] A high entropy boride ceramic nanopowder, the preparation method of which comprises the following steps:

[0051] 1) 4.42 g of Ta2O5 powder, 2.66 g of Nb2O5 powder, 2.46 g of ZrO2 powder, 1.60 g of TiO2 powder, 11.14 g of boron oxide and 17.35 g of magnesium powder were added to an agate mortar and manually ground for 60 min, then 6.72 g of NaF was added and manually ground for 60 min, and then pre-pressed into a sheet at a pressure of 30 MPa to prepare a mixed powder tablet, and 4.00 g of titanium powder and 1.00 g of carbon powder were added to an agate mortar and manually ground for 60 min to prepare an igniter;

[0052] 2) Place the mixed powder tablet into a rectangular graphite mold with a length of 15 cm and a width of 5 cm, and place the igniter at the front end of the graphite mold in contact with one side of the mixed powder tablet. Then take a section of molybdenum wire with a length of 20 cm and a diameter of 0.4 mm and pass it through the igniter. Then place the graphite mold in the combustion reactor, connect the two ends of the molybdenum wire to the internal electrodes, close the hatch of the combustion reactor, and then evacuate it to make the vacuum pressure counter value reach 1.0×10 -4 Pa, maintain vacuum for 10 minutes (observe whether the vacuum gauge indication changes. If there is no change, it means that the system is well sealed. If there is a change, further sealing operation is required), then introduce argon to normal pressure, and then pass 30A current through the molybdenum wire for 15 seconds and then turn off the power supply. Violent combustion and thick smoke are observed in the combustion reactor, and then naturally cool to room temperature to obtain combustion products;

[0053] 3) The combustion products are crushed and ground into fine particles after removing the surface part in contact with the igniter. The particles are then washed three times with deionized water at 70°C and hydrochloric acid with a concentration of 1 mol / L, each time for 5 hours. The filtered solid is placed in a drying oven at 40°C and dried for 3 hours to obtain high entropy boride ceramic nanopowder (denoted as HEB-4).

[0054] Performance Testing:

[0055] 1) The X-ray diffraction (XRD) pattern of the high entropy boride ceramic nanopowder (HEB-4) in this embodiment is as follows: Figure 1 shown.

[0056] Depend on Figure 1 It can be seen that the high entropy boride ceramic nanopowder in this embodiment is a pure phase and does not contain other impurity phases.

[0057] 2) The STEM-EDS spectrum element distribution diagram of the high entropy boride ceramic nanopowder (HEB-4) in this embodiment is as follows: Figure 2 As shown (A in the figure).

[0058] Depend on Figure 2It can be seen that the high entropy boride ceramic nanopowder in this embodiment is granular, with an average particle size of about 95 nm, and the four constituent elements of Ta, Nb, Zr and Ti are evenly distributed. After testing, the oxygen impurity content is only 2.5%.

[0059] 3) 100 mL of a mixed solution of 100 mg / L tetracycline (TC) and 5 mmol / L persulfate (PS) was added to a beaker of 250 mL, and then 0.5 g of the high entropy boride ceramic nanopowder (HEB-4) in the present embodiment was added, and then stirred continuously at room temperature at a speed of 300 r / min for 10 h by a magnetic stirrer, and then the supernatant was filtered with a polytetrafluoroethylene filter (pore size of 0.22 μm), and then the concentration of tetracycline in the filtrate was determined by a UV-visible spectrophotometer at a maximum absorption wavelength λ of 356 nm (the experimental group without PS was set as a control), and the degradation efficiency of tetracycline was calculated, and the calculation formula was: Degradation efficiency (%) = (C0-C1) / C0×100%, C0 is the initial concentration of tetracycline, C1 is the final concentration of tetracycline, and the degradation efficiency test results of the high entropy boride ceramic nanopowder (HEB-4) activated PS to catalyze the degradation of tetracycline are shown in the figure. Figure 3 (HEBs in the figure represent the high entropy boride ceramic nanopowders in Examples 1 to 3).

[0060] Depend on Figure 3 It can be seen that the high entropy boride ceramic nanopowder in this embodiment is used to activate PS to catalyze the degradation of a tetracycline solution with a concentration of 100 mg / L for 10 hours, and the degradation efficiency is 94%, while the degradation efficiency is only 39% when no PS is added.

[0061] Embodiment 2:

[0062] A high entropy boride ceramic nanopowder, the preparation method of which comprises the following steps:

[0063] 1) 5.30 g of Ta2O5 powder, 3.19 g of Nb2O5 powder, 2.96 g of ZrO2 powder, 1.82 g of Cr2O3 powder, 1.92 g of TiO2 powder, 16.71 g of boron oxide and 26.77 g of magnesium powder were added to an agate mortar and manually ground for 60 min, then 13.60 g of NaF was added and manually ground for 60 min, and then pre-pressed into a sheet at a pressure of 40 MPa to prepare a mixed powder tablet, and 4.00 g of titanium powder and 1.00 g of carbon powder were added to an agate mortar and manually ground for 60 min to prepare an igniter;

[0064] 2) Place the mixed powder tablet into a rectangular graphite mold with a length of 15 cm and a width of 10 cm, and place the igniter at the front end of the graphite mold in contact with one side of the mixed powder tablet. Then take a section of molybdenum wire with a length of 22 cm and a diameter of 0.5 mm and pass it through the igniter. Then place the graphite mold in the combustion reactor, connect the two ends of the molybdenum wire to the internal electrodes, close the hatch of the combustion reactor, and then evacuate it to make the vacuum pressure counter value reach 1.0×10 -4 Pa, maintain vacuum for 10 minutes (observe whether the vacuum gauge indication changes. If there is no change, it means that the system is well sealed. If there is a change, further sealing operation is required), then introduce argon to normal pressure, and then pass a 40A current through the molybdenum wire for 10 seconds and then turn off the power supply. Violent combustion and thick smoke are observed in the combustion reactor, and then naturally cool to room temperature to obtain combustion products;

[0065] 3) The combustion products are crushed and ground into fine particles after removing the surface part in contact with the igniter. The particles are then washed 4 times with deionized water at 80°C and hydrochloric acid with a concentration of 2 mol / L, each time for 4 hours. The filtered solid is placed in a drying oven and dried at 40°C for 3 hours to obtain high entropy boride ceramic nanopowder (denoted as HEB-5).

[0066] Performance Test:

[0067] 1) The XRD pattern of the high entropy boride ceramic nanopowder (HEB-5) in this embodiment is as follows: Figure 1 shown.

[0068] Depend on Figure 1 It can be seen that the high entropy boride ceramic nanopowder in this embodiment is a pure phase and does not contain other impurity phases.

[0069] 2) The STEM-EDS spectrum element distribution diagram of the high entropy boride ceramic nanopowder (HEB-5) in this embodiment is as follows: Figure 2 As shown (B in the figure).

[0070] Depend on Figure 2 It can be seen that the high entropy boride ceramic nanopowder in this embodiment is granular, with an average particle size of about 87 nm, and the five constituent elements of Ta, Nb, Zr, Cr and Ti are evenly distributed. After testing, the oxygen impurity content is only 2.7%.

[0071] 3) The degradation efficiency test of the high entropy boride ceramic nanopowder (HEB-5) in this embodiment to activate PS to catalyze the degradation of tetracycline (the test process is the same as in Example 1). The results are shown in the figure Figure 3 shown.

[0072] Depend on Figure 3It can be seen that the high entropy boride ceramic nanopowder in this embodiment is used to activate PS to catalyze the degradation of a tetracycline solution with a concentration of 100 mg / L for 10 hours, and the degradation efficiency is 89%, while the degradation efficiency is only 37% when no PS is added.

[0073] Embodiment 3:

[0074] A high entropy boride ceramic nanopowder, the preparation method of which comprises the following steps:

[0075] 1) 4.42 g of Ta2O5 powder, 2.66 g of Nb2O5 powder, 2.46 g of ZrO2 powder, 1.52 g of Cr2O3 powder, 1.60 g of TiO2 powder, 4.21 g of HfO2 powder, 16.71 g of boron oxide and 28.17 g of magnesium powder were added to an agate mortar and manually ground for 60 min, then 17.13 g of NaF was added and manually ground for 60 min, and then pre-pressed into a sheet at a pressure of 50 MPa to prepare a mixed powder tablet, and 4.00 g of titanium powder and 1.00 g of carbon powder were added to an agate mortar and manually ground for 60 min to prepare an igniter;

[0076] 2) Place the mixed powder tablet into a rectangular graphite mold with a length of 20 cm and a width of 10 cm, and place the igniter at the front end of the graphite mold in contact with one side of the mixed powder tablet. Then take a section of molybdenum wire with a length of 25 cm and a diameter of 0.6 mm and pass it through the igniter. Then place the graphite mold in the combustion reactor, connect the two ends of the molybdenum wire to the internal electrodes, close the hatch of the combustion reactor, and then evacuate it to make the vacuum pressure counter value reach 1.0×10 -4 Pa, maintain vacuum for 10 minutes (observe whether the vacuum gauge indication changes. If there is no change, it means that the system is well sealed. If there is a change, further sealing operation is required), then introduce argon to normal pressure, and then pass a 50A current through the molybdenum wire for 5s and then turn off the power supply. Violent combustion and thick smoke are observed in the combustion reactor, and then naturally cool to room temperature to obtain combustion products;

[0077] 3) The combustion products are crushed and ground into fine particles after removing the surface part in contact with the igniter. The particles are then washed 5 times with deionized water at 90°C and hydrochloric acid with a concentration of 3 mol / L, each time for 3 hours. The filtered solid is placed in a drying oven at 40°C and dried for 3 hours to obtain high entropy boride ceramic nanopowder (denoted as HEB-6).

[0078] Performance Test:

[0079] 1) The XRD pattern of the high entropy boride ceramic nanopowder (HEB-6) in this embodiment is as follows: Figure 1 shown.

[0080] Depend on Figure 1It can be seen that the high entropy boride ceramic nanopowder in this embodiment is a pure phase and does not contain other impurity phases.

[0081] 2) The STEM-EDS spectrum element distribution diagram of the high entropy boride ceramic nanopowder (HEB-6) in this embodiment is as follows: Figure 2 As shown (C in the figure).

[0082] Depend on Figure 2 It can be seen that the high entropy boride ceramic nanopowder in this embodiment is granular, with an average particle size of about 85 nm, and the six constituent elements of Ta, Nb, Zr, Cr, Ti and Hf are evenly distributed. After testing, the oxygen impurity content is only 2.9%.

[0083] 3) The degradation efficiency test of PS catalytic degradation of tetracycline by high entropy boride ceramic nanopowder (HEB-6) in this embodiment (the test process is the same as that in Example 1) is shown in the figure below: Figure 3 shown.

[0084] Depend on Figure 3 It can be seen that the high entropy boride ceramic nanopowder in this embodiment is used to activate PS to catalyze the degradation of a tetracycline solution with a concentration of 100 mg / L for 10 hours, and the degradation efficiency is 91%, while the degradation efficiency is only 38% when no PS is added.

[0085] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing high entropy boride ceramic nanopowder, characterized in that: The following steps are involved: 1) mixing metal oxide powder, boron oxide powder, magnesium powder and NaF, grinding them and pre-pressing them into sheets to make mixed powder tablets, and mixing titanium powder and carbon powder, grinding them to make an ignition agent; 2) adding the mixed powder tablet and the igniter into a graphite mold, taking a section of molybdenum wire and passing it through the igniter, and then placing the graphite mold in a protective atmosphere, and then electrically heating the molybdenum wire to burn the igniter to ignite the mixed powder tablet to carry out a combustion synthesis reaction to obtain a combustion product; 3) crushing, grinding, washing, pickling and drying the combustion products to obtain high entropy boride ceramic nanopowder; The metal oxide powder is composed of at least four of Ta2O5, Nb2O5, Cr2O3, ZrO2, TiO2 and HfO2 in an equal molar ratio; The ratio of the total molar amount of the metal oxide powder to the molar amount of the boron oxide powder is 1:2; The ratio of the total molar amount of oxygen atoms in the metal oxide powder and the boron oxide powder to the molar amount of magnesium powder is 1:1.7-1.9; The molar ratio of the boron oxide powder to NaF is 1:2.0-3.4; Step 2) The current of the electric heating is 30A to 50A, and the power-on time is 5s to 15s.

2. The preparation method according to claim 1, characterized in that: The Ta2O5, Nb2O5, Cr2O3, ZrO2, TiO2 and HfO2 are all in powder form with a purity of ≥99.9% and a particle size of 100nm to 300nm; the purity of the boron oxide powder is ≥99.9% and a particle size of 1μm to 3μm; the purity of the magnesium powder is ≥99.5% and a particle size of 1μm to 3μm; the purity of the NaF is ≥98.0%; the purity of the titanium powder is ≥99.9% and a particle size of 1μm to 3μm; the purity of the carbon powder is ≥99.0% and a particle size of <48μm.

3. The preparation method according to claim 1, characterized in that: The pre-compression into tablets in step 1) is carried out under a pressure of 30 MPa to 50 MPa.

4. The preparation method according to claim 1, characterized in that: Step 2) The graphite mold is rectangular, 15 cm to 20 cm long and 5 cm to 10 cm wide.

5. A high entropy boride ceramic nanopowder, characterized in that: The high entropy boride ceramic nanopowder is prepared by the preparation method described in any one of claims 1 to 4; the average particle size of the high entropy boride ceramic nanopowder is 85nm to 95nm; the oxygen impurity content of the high entropy boride ceramic nanopowder is 2.5% to 2.9%.

6. Use of the high entropy boride ceramic nanopowder as claimed in claim 5 in catalytic degradation of tetracycline by activated persulfate.